2020
DOI: 10.1111/1759-7714.13548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 3‐minute chair rise test as part of preoperative evaluation for patients with non‐small cell lung cancer

Abstract: Background Peak oxygen uptake (trueV˙O2peak) measured by a cardiopulmonary exercise test (CPX) is the gold‐standard for predicting surgical risk in patients with non‐small cell lung cancer (NSCLC). The 3‐minute chair rise test (3CRT) is a simple test requiring minimal resources. This study aimed to determine the ability of 3CRT to predict trueV˙O2peak in patients with NSCLC. Methods Retrospective data from CPX and 3CRT carried out in 36 patients with NSCLC between March 2018 and February 2019 were included. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We placed less weight on the final five studies—as the methodological quality was uncertain, or because methodological quality was considered to be poor on our risk of bias and applicability tool, though the findings from all these additional studies were similar to the above ones. These studies were Gruet et al (a prospective correlation study from France in 25 patients with cystic fibrosis, which concluded that the 1MSTST may be used as an alternative to the 6MWT and CPET for assessing exertional desaturation) [ 47 ]; Morita et al (a study in 23 patients with COPD which showed good correlation between various exercise desaturation tests) [ 48 ]; Kohlbrenner et al (a retrospective study from Switzerland in 38 lung transplant candidates which concluded that the 1MSTST is a safe alternative to 6MWT in such patients despite lower desaturation nadirs) [ 49 ]; Crook et al (a prospective study in 21 COPD patients which concluded that 1MSTST is a safe and accurate alternative to 6MWT); and Azzi et al (a retrospective study in 36 lung cancer patients whose main aim was to compare a 3-min chair-to-rise test, 3MCTRT, with the CPET in terms of maximal exercise capacity but which also found high correlation with the level of oxygen desaturation achieved) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…We placed less weight on the final five studies—as the methodological quality was uncertain, or because methodological quality was considered to be poor on our risk of bias and applicability tool, though the findings from all these additional studies were similar to the above ones. These studies were Gruet et al (a prospective correlation study from France in 25 patients with cystic fibrosis, which concluded that the 1MSTST may be used as an alternative to the 6MWT and CPET for assessing exertional desaturation) [ 47 ]; Morita et al (a study in 23 patients with COPD which showed good correlation between various exercise desaturation tests) [ 48 ]; Kohlbrenner et al (a retrospective study from Switzerland in 38 lung transplant candidates which concluded that the 1MSTST is a safe alternative to 6MWT in such patients despite lower desaturation nadirs) [ 49 ]; Crook et al (a prospective study in 21 COPD patients which concluded that 1MSTST is a safe and accurate alternative to 6MWT); and Azzi et al (a retrospective study in 36 lung cancer patients whose main aim was to compare a 3-min chair-to-rise test, 3MCTRT, with the CPET in terms of maximal exercise capacity but which also found high correlation with the level of oxygen desaturation achieved) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…CPET has now been integrated to pretreatment risk assessment algorithms 34 and helps guide respiratory rehabilitation programs worldwide 35 . However, this test still suffers from a lack of accessibility in some centres due to resource limitations, 9,36 and poses the risk of over‐estimating risks in up to 30% of patients who cannot provide the necessary maximum effort to ensure validity of VO 2 measurements 37 . Additional tools to identify patients with respiratory fragility who could potentially benefit from rehabilitation programs are therefore needed 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…We placed less weight on the nal ve studies -as the methodological quality was uncertain, or because methodological quality was considered to be poor on our risk of bias and applicability tool, though the ndings from all these additional studies were similar to the above ones. These studies were: Gruet et al (a prospective correlation study from France in 25 patients with cystic brosis, which concluded that the 1MSTST may be used as an alternative to the 6MWT and CPET for assessing exertional desaturation) [47]; Morita et al (a study in 23 patients with COPD which showed good correlation between various exercise desaturation tests) [48]; Kohlbrenner et al (a retrospective study from Switzerland in 38 lung transplant candidates which concluded that the 1MSTST is a safe alternative to 6MWT in such patients despite lower desaturation nadirs) [49]; Crook et al (a prospective study in 21 COPD patients which concluded that 1MSTST is a safe and accurate alternative to 6MWT); and Azzi et al (a retrospective study in 36 lung cancer patients whose main aim was to compare a 3-minute chair-to-rise test, 3MCTRT, with the CPET in terms of maximal exercise capacity but which also found high correlation with the level of oxygen desaturation achieved) [50].…”
Section: Validation Of Tests For Exertional Hypoxia In Conditions Othmentioning
confidence: 99%